Analisis Konseptual Matematis terhadap Dua Game Pembelajaran Berbasis Aljabar Linear - Hilda Sari Laonga; Ade Lia Rahmaningrum; Tasya Agustin Hermawati; Fatimah Azzahra; Habib Giynastiar (Perspectives in Mathematics and Applications, 2026)
This study aims to analyse mathematical representations in two interactive media: vector unknown and GeoGebra-based linear transformation simulation, within the context of applied linear algebra learning. Using a qualitative-descriptive approach, this study examines the consistency of symbolic structure, spatial visualisation, and applicative relevance across the two media. The results of the analysis show that Vector Unknown is effective at representing a combination of linear and result spaces, whereas GeoGebra excels at visualising matrix and determinant transformations. Both support conceptual understanding and modelling skills that are essential in the fields of Engineering, computer graphics, and spatial systems. The study confirms that interactive media can bridge the gap between abstraction and real-world applications, encouraging inquiry-based learning. The limitations of this study include the limited scope of the concept and the absence of empirical validation based on user performance. Therefore, further research is recommended to expand the media and the scope of concepts.